Effects of bile acids supplemented into low fishmeal diet on growth, molting, and intestinal health of Pacific white shrimp, Litopenaeus vannamei - Xiaoyue Li; Menglin Shi; Liutong Chen; Shuang Zhang; Shuyan Chi; Xiaohui Dong; Junming Deng; Beiping Tan; Shiwei Xie (Aquaculture Reports, 2023)
This study aimed to evaluate the replacement of fishmeal with soybean and cottonseed protein concentrates and dietary supplementation of bile acids on the growth performance, immunity, molting, and intestinal health of Litopenaeus vannamei. Six diets were formulated: high fishmeal diet (HFM, 25% fishmeal), low fishmeal diet (LFM, 10% fishmeal), LBA1 (LFM + 0.15 g kg−1 bile acids), LBA2 (LFM + 0.3 g kg−1 bile acids), LBA3 (LFM + 0.6 g kg−1 bile acids), and LBA4 (LFM + 0.9 g kg−1 bile acids). Each diet was randomly assigned to triplicate groups of 40 shrimp (initial mean weight: 0.25 ± 0.00 g) per tank. After 50 d of the feeding trial, the final body weight significantly increased in shrimp fed the LBA4 diet compares to those fed the LFM diet (p < 0.05). Shrimp in the LBA1 group showed significantly increased imd, crustin, and myd88 expressions than those in the HFM group (p < 0.05). The shrimp fed the LBA2 diet had significantly increased expression of pen, imd, crustin, myd88, and alf compared to those fed the HFM diet, while in the LBA3 group, only crustin expression increased compared to the HFM group (p < 0.05). Moreover, bile acids could enhance the molting-related gene expression in the intestine and hepatopancreas. In the intestine, shrimp in the LBA3 group presented significantly upregulated nuclear hormone receptor E75-like (e75) and ecdysone receptor-like (ecr) expression than those in the HFM group, while in the LBA4 group, only ecr expression increased (p < 0.05). In the hepatopancreas, shrimp fed the LBA2 and LBA4 diets had significantly enhanced the ecr and chitinase (chi2) expression than those fed the LFM diet (p < 0.05). Additionally the chi2 expression was significantly higher in the LBA3 group than in the LFM group (p < 0.05). Low fishmeal diets significantly reduced the intestinal fold height, fold width, and thickness of circular muscle layers in shrimp (p < 0.05), whereas bile acid supplementation could avoid this intestinal damage. Dietary supplementation of bile acids increased the diversity and the richness of the intestinal flora: The abundance of Planctomycetes and Verrucomicrobia significantly increased in shrimp fed the LBA1 and LBA3 diets compared to those fed the LFM diet (p < 0.05). Bile acid supplementation reduced the relative intestinal abundance of Pseudoalteromonas and Haloferula compare with HFM group (p < 0.05). In summary, bile acid supplementation upregulated the expression of immune and molting-related genes, improved intestine health, and enhanced the growth performance of shrimp fed a low fishmeal diet.